2020
DOI: 10.3892/ijmm.2020.4777
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates cerebral ischemia‑reperfusion injury in rats through the inhibition of calcium‑sensing receptor‑mediated apoptosis

Abstract: cerebral ischemia-reperfusion injury (cIRI), caused by the reperfusion of blocked vessels following ischemic stroke, can lead to secondary brain injury. Throughout cIRI, apoptosis serves an important role. Astragaloside IV is a potential neuroprotectant that alleviates cIRI by inhibiting apoptosis. The calcium-sensing receptor (caSR) is a G-protein-coupled receptor, the activation of which aggravates ischemia-reperfusion injury. The aim of the present study was to investigate whether the protective effect of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…To identify whether p-ERK1/2 held a critical function on IH-induced cell apoptosis and synaptic plasticity de cit, PD98059, a potent and selective MEK inhibitor, which can inhibit ERK1/2 signaling, was selected to pretreat PC12 cells. Firstly, according to previous research [24]. several different concentrations of inhibitors in our experiment were selected.…”
Section: Casr Modulated the Synaptic Plasticity In Pc12 Cells With Ih...mentioning
confidence: 99%
See 1 more Smart Citation
“…To identify whether p-ERK1/2 held a critical function on IH-induced cell apoptosis and synaptic plasticity de cit, PD98059, a potent and selective MEK inhibitor, which can inhibit ERK1/2 signaling, was selected to pretreat PC12 cells. Firstly, according to previous research [24]. several different concentrations of inhibitors in our experiment were selected.…”
Section: Casr Modulated the Synaptic Plasticity In Pc12 Cells With Ih...mentioning
confidence: 99%
“…ERK1/2, as a subfamily of mitogen-activated protein kinases (MAPKs), is generally thought to be involved in cell apoptosis, proliferation and synaptic plasticity [21,22]. Further studies indicated that CaSR activation aggravates the apoptosis and the change of synaptic plasticity in hippocampal neurons during H/R [11,23] and the [Ca 2+ ]i overload induced by the activation of CaSR contributes to the apoptosis of PC12 cells in oxygen and glucose deprivation/reoxygenation [24]. However, it remains unclear whether CaSR holds a function on CIH-induced apoptosis and synaptic plasticity in hippocampal neurons by PKC-ERK1/2 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The bioinformatics analysis results correspond with our findings. Additionally, Chun Wang and Shu‐Jin Du's studies demonstrated that NPS‐2143 had a neural protection effect in rat models, which suggests that NPS‐2143 might have the permeability of BBB 38,39 . However, we did not investigate the BBB permeability of NPS‐2143 in intracranial glioma mice mode.…”
Section: Discussionmentioning
confidence: 88%
“…It has been found that during cerebral ischemia-reperfusion, the protein expression of CaSR and calcium influx increase. Astragaloside IV can inhibit the protein expression of CaSR after ischemia-reperfusion injury to reduce calcium reflux ( Du et al, 2021 ). Radix Astragali exerts a protective effect not only on neurons but also against ischemic apoptosis of neural stem cells.…”
Section: Mechanism Underlying the Amelioration Of Ischemia-reperfusion Injury By Astragaloside IVmentioning
confidence: 99%